



 
Hi, This is an exercise with the distributive law which says that for any numbers $a, b$ and $c$, $a(b + c) = ab + ac.$ I an going to illustrate with a different question,
To use the distributive law I will take $a = 3x  5, b = 2x \mbox{ and }c = 3.$ with this I get \[(3 x  5)(2x + 3) = (3x  5) \times 2x + (3x  5) \times 3 = 6x^2 10 x + 9x  15 = 6x^2 x  15.\] Try this with your problem. It simplifies to something simpler than mine. Penny  


Math Central is supported by the University of Regina and the Imperial Oil Foundation. 